Effect of Compost Mix of Mexican Sunflower (Tithonia diversifolia) Green Manure and Poultry Bone Meal on Productivity and Nutritional Quality of Red Russian Kale (Brassicae napus var. pabularia) - Sembiring, Krisman; Banjarnahor, Dina (Universitas Panji Sakti, 2024)
Mexican sunflower leaves (Tithonia diversifolia) contain high levels of nitrogen (N) and potassium (K). Combining it with poultry bone meal rich in phosphorus may produce a compost mix containing high N, P, and K. This research aims to compare the effect of this compost mix on the productivity and nutritional quality of Red Russian kale. The research was conducted at the Faculty of Agriculture and Business, Satya Wacana Christian University, from December 2023 to June 2024. Treatments tested were: CM-N100 (compost mix containing 100% of the required N); CM-P100 (compost mix containing 100% of the required P); CM-K100 (compost mix containing 100% of the required K); IF-NPK100 (inorganic fertilizer containing 100% of the required N, P, and K); and NPK0 (zero fertilization). Plant height, number of leaves, crown diameter, biomass, harvest index, vitamin C, total anthocyanins, total chlorophyll, and carotenoids were measured then analyzed using the ANOVA test and Tukey-test (P<0.05). CM-P100 and CM-K100 (180-200 g of compost mix per pot) resulted in the highest yield, vitamin C, chlorophyll, and carotenoids. However, both treatments resulted in the lowest anthocyanins content. CM-N100 (95 g of compost mix per pot) resulted in the highest anthocyanin accumulation (92.84 mg/100 g). IF-NPK100 has supplied Red Russian kale with adequate N, P, and K but resulted in lower yield and nutritional quality compared to CM-P100 and CM-K100. This indicated that higher nitrogen supply might still boost the productivity and nutritional content of Red Russian kale. Zero fertilization resulted in the least productive and nutritious kale leaves.